Preventing Conflicts of Interest of NFL Team Physicians - Rothstein, Mark A. (The Hastings Center report, 2016)
At least since the time of Hippocrates, the physician-patient relationship has been the paradigmatic ethical arrangement for the provision of medical care. Yet, a physician-patient relationship does not exist in every professional interaction involving physicians and individuals they examine or treat. There are several “third-party” relationships, mostly arising where the individual is not a patient and is merely being examined rather than treated, the individual does not select or pay the physician, and the physician's services are provided for the benefit of another party. Physicians who treat NFL players have a physician-patient relationship, but physicians who merely examine players to determine their health status have a third-party relationship. As described by Glenn Cohen et al., the problem is that typical NFL team doctors perform both functions, which leads to entrenched conflicts of interest. Although there are often disputes about treatment, the main point of contention between players and team physicians is the evaluation of injuries and the reporting of players’ health status to coaches and other team personnel. Cohen et al. present several thoughtful recommendations that deserve serious consideration. Rather than focusing on their specific recommendations, however, I would like to explain the rationale for two essential reform principles: the need to sever the responsibilities of treatment and evaluation by team physicians and the need to limit the amount of player medical information disclosed to teams.